2012
DOI: 10.1186/1757-2215-5-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of melatonin as an antioxidant in the follicle

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is secreted during the dark hours at night by pineal gland, and it regulates a variety of important central and peripheral actions related to circadian rhythms and reproduction. It has been believed that melatonin regulates ovarian function by the regulation of gonadotropin release in the hypothalamus-pituitary gland axis via its specific receptors. In addition to the receptor mediated action, the discovery of melatonin as a direct free radical scavenger has greatly bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
176
2
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(195 citation statements)
references
References 63 publications
6
176
2
11
Order By: Relevance
“…Oxidative stress reduces oocyte quality [18][19][20] and impairs endometrial receptivity [21]. Together, these findings strongly suggest that oxidative stress contributes to infertility in endometriosis patients.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Oxidative stress reduces oocyte quality [18][19][20] and impairs endometrial receptivity [21]. Together, these findings strongly suggest that oxidative stress contributes to infertility in endometriosis patients.…”
Section: Introductionmentioning
confidence: 63%
“…Melatonin is a powerful free radical scavenger and a broad-spectrum antioxidant [31,32]. We previously demonstrated that melatonin is present in human ovarian follicles and that its concentration increases during follicular growth [18][19][20]. We also reported that melatonin is taken up into the follicular fluid from the blood, and that it protects oocytes from ROS within the follicle during ovulation Figure 1 Tumor necrosis factor alpha (TNFα) concentrations in follicular fluids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive oxygen species (ROS) and apoptosis are involved with a number of reproductive events, including folliculogenesis, follicular atresia, ovulation, oocyte maturation, and corpus luteum (CL) formation (Tamura et al, 2009). The ROS produced within the follicles, especially during the ovulation process, were scavenged by melatonin and reduced oxidative stress may be involved with oocyte maturation and embryo development (El-Raey et al, 2011;Tamura et al, 2012). We suggest that melatonin was involved with the growth and maturation of ovarian follicles and it also participated in the growth of oocytes.…”
Section: Discussionmentioning
confidence: 92%
“…Positive are those related to ROS involvement in energy production, phagocytosis, regulation of cell growth and intercellular signaling, and synthesis of biologically active compounds [7]. While physiological levels of oxygen are necessary for cells to live, the presence of excess ROS, such as superoxide radical (O 2 and hydrogen peroxide (H 2 O 2 ), can also have considerable impact on early embryonic viability, as these compounds have been implied to be involved in nuclear fragmentation and apoptosis, mitochondrial degeneration, developmental block during early cleavage stage and mitotic arrest [8][9][10].…”
Section: Introductionmentioning
confidence: 99%